The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00464-005-0470-5
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless and stapleless laparoscopic splenectomy using radiofrequency

Abstract: The use of LigaSure, and the semilateral position, results in a gain of time and safety. Furthermore, average intraoperative bleeding is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 33 publications
3
84
0
3
Order By: Relevance
“…[16,17] As mentioned above, in a series of LA in which the LigaSure ® device was used the reported operation times were between 57 to 123 minutes and mean sizes of the adrenal masses were between 40 to 62 mm. [13][14][15] In the present study, the mean operation time and mean size of the adrenal masses in the LigaSure ® device group were 90.2 (range; 50 to 150) minutes and 37.2 (range; 15 to 72) mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] As mentioned above, in a series of LA in which the LigaSure ® device was used the reported operation times were between 57 to 123 minutes and mean sizes of the adrenal masses were between 40 to 62 mm. [13][14][15] In the present study, the mean operation time and mean size of the adrenal masses in the LigaSure ® device group were 90.2 (range; 50 to 150) minutes and 37.2 (range; 15 to 72) mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tüm diseksiyonun Ligasure® ile yapıldığı serilerde kanama miktarının az olduğu, operasyon süresinin kısaldığı bildirilmiş-tir (19)(20)(21)(22) .…”
Section: Discussionunclassified
“…It has been observed that 31% of patients who had an overwhelming postsplenectomy infection (OPSI) had previously received the appropriate pneumococcal vaccine. OPSIs are rare but well-described, life-threatening events that can occur after splenectomy (131), (132). The incidence of postoperative infection has been estimated to be 3.2%, with a mortality rate of 1.3% (131).…”
Section: Minimally Invasive Splenectomy In Advanced Ovarian Cancermentioning
confidence: 99%